Transcriptomic and Metabolomic Responses of Rice Plants to Cnaphalocrocis medinalis Caterpillar Infestation - Yuqi Wang; Qingsong Liu; Lixiao Du; Eric M. Hallerman; Yunhe Li (Insects, 2020)
Interactions between plants and insect herbivores are important determinants of plant productivity in cultivated and natural agricultural fields. The rice leaf folder (Cnaphalocrocis medinalis) causes tremendous damage to rice production in Asian countries. However, little information is available about how rice plants defend themselves against this destructive pest at molecular and biochemical levels. Here, we observed the transcriptomic and metabolomic differences in rice leaves after 0, 1, 6, 12, and 24 h of being fed by C. medinalis using RNA sequencing and metabolome profiling. Transcriptional analyses showed that gene expression responds rapidly to leaf folder infestation, with the most significant transcriptional changes occurring within 6 h after the initiation of feeding. Metabolite abundance changed more slowly than gene expression. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses indicated that the rice transcriptional response to infestation involved genes encoding protein kinases, transcription factors, biosynthesis of secondary metabolites, photosynthesis, and phytohormone signaling. Moreover, the jasmonic acid-dependent signaling pathway triggered by leaf folder herbivory played a vital role in rice defense against this pest. Taken together, our results provide comprehensive insights into the defense system of rice to this species and may inform the development of insect-resistant rice varieties.